Laser-based conversion electron Mössbauer spectroscopy of 229ThO2 - Ricky Elwell; James E. S. Terhune; Christian Schneider; Harry W. T. Morgan; Hoang Bao Tran Tan; Udeshika C. Perera; Daniel A. Rehn; Marisa C. Alfonso; Lars von der Wense; Benedict Seiferle; Kevin Scharl; Peter G. Thirolf; et al. (Nature, 2025)
Abstract The exceptionally low-energy 229 Th nuclear isomeric state is expected to provide several new and powerful applications 1,2 , including the construction of a robust and portable solid-state nuclear clock 3 , perhaps contributing to a redefinition of the second 4 , exploration of nuclear superradiance 5,6 and tests of fundamental physics 7–10 . Further, analogous to the capabilities of traditional Mössbauer spectroscopy, the sensitivity of the nucleus to its environment can be used to realize laser Mössbauer spectroscopy and, with it, new types of strain and temperature sensors 3,11 and a new probe of the solid-state environment 12,13 , all with excellent sensitivity. However, current models for examining the nuclear transition in a solid require the use of a high-bandgap, vacuum ultraviolet (VUV) transmissive host, severely limiting the applicability of these techniques. Here we report the first, to the authors’ knowledge, demonstration of laser-induced conversion electron Mössbauer spectroscopy (CEMS) of the 229 Th isomer in a thin ThO 2 sample whose bandgap (approximately 6 eV) is considerably smaller than the nuclear isomeric state energy (8.4 eV). Unlike fluorescence spectroscopy of the 229 Th isomeric transition, this technique is compatible with materials whose bandgap is less than the nuclear transition energy, opening a wider class of systems to study and the potential of a conversion-electron-based nuclear clock.